Implementation of Data-Based Pastoral Through BIDUK Application to Realize the Living Gods People - Palinoan*, Frans Fandy; Tandiangga, Patrio; Arnoltus, Cornelius (Riwayat: Educational Journal of History and Humanities, 2023)
The Church is a community of God's people that has a divine and human character because it consists of people who live in a certain time, place and time. Departing from its human characteristics, the Church Pastoral Pattern is expected to be able to adapt to the situation and real needs of the people. Pastoral actors are expected to be able to work based on data, not assumptions or interpretations without foundation. On the basis of this understanding, the author tries to implement data-based pastoral through the BIDUK application which has begun to be used in the Archdiocese of Makassar, especially in the Renya Rosari Deri Parish. The research method used in this study is a quantitative method in which the author will collect parishioner data recorded in the BIDUK application and then process it into a report that describes the real condition of the parishioners. After the author gets a complete picture of the real condition of the people, then theological analysis and reflection are carried out. From the analysis and theological reflection, the author will provide pastoral advice that is expected to provide answers to the needs of the people.